Case Study on the Strategic Digitization of a Retail Organization, Emphasizing the Tactical Integration and Embrace of Advanced Technological Initiatives - Divya Gupta; Dr. Bala Krishnamoorthy; Dr. O.P. Wali, (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2024)
The purpose of the research is to study the transformation of a retail firm in India that has undergone digitization by embracing advanced technological initiatives - implementation of Point of Sales, CRM solution, Endless Isle, watsapp shopping, Click and Collect in their stores with an objective of sales growth from the same set of stores. The authors have studied the end-to- end journey of implementation of these initiatives in the 500 exclusive business outlets in India of the organization. The phases of the transformation considered are – 1)Factors that have triggered the embracing of thesetechnological initiatives 2) digital readiness as an antecedent to the adoption of the technology and 3) adoption of transformationinitiatives in the organization. The authors have conducted in-depth semi-structured interviews of fourteen organizationexecutives in scope. These experts have been part of thetransformation of this organization. They had either beeninstrumental in making decisions or actual users of the digitalinitiatives. The data was content analyzed for themes. Postdiscussions with the experts on the three phases, themes wereidentified across the phases. Salient findings from the researchinclude the support from leadership on initiating the program toimplement technology initiatives, organization-wide communication including the adoption of initiatives, the impact ofthe Pandemic on digital transformation in the firm in scopeimportance of adoption and tracking adoption during this journeyand more. The research plays an important part for academiciansto understand that apart from triggering digital transformationprojects in organizations, what else should companies do toincrease readiness and adoption of initiatives in organizations.From this study, new theoretical contributions to the existing bodyof knowledge have been identified which are related to technologyTransformation on all the 3 phases of digital transformation fororganizations – Drivers which trigger digital transformation,digital readiness as an antecedent to digital transformation andadoption of technological initiatives by organizations. Thefindings from the study would help managers leading digitaltransformation initiatives in their firms. The findings would helpthe managers understand what went right and what couldpotentially go wrong during the implementation of initiatives inorganizations. The study findings can act as a guiding principle workbook for organizations that are planning to embark on the journey of launching transformation in their organizations by focusing on internal and external factors. The study also sheds light on how organizations are driven by external catastrophic events like Covid-19 pandemic. The study findings will also be relevant for the change leaders of organizations to understand how to be the chief narrator of digital transformation.